Implementasi Modul Pembelajaran Berbasis PjBL Terhadap Kemampuan Berfikir Kreatif Siswa pada Materi Bangun Ruang Melalui Pembuatan Miniatur Bangunan Adat Batak Toba di SMP - Hutapea, Jernyta Futri Agustina Br.; Tambunan, Hardi; Pangaribuan, Firman (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the effect of implementing a Project Based Learning (PjBL) based learning module on students' creative thinking abilities in solid geometry material through the creation of a Batak Toba traditional building miniature in junior high school. This study uses a quantitative approach with a quasi-experimental design of the non-equivalent control group type. The research sample consisted of two classes, namely the experimental class that received treatment using the PjBL-based module and the control class that used conventional learning. Data collection techniques were conducted through pretests and posttests using mathematical creative thinking ability test instruments referring to indicators of fluency, flexibility, originality, and elaboration. Data were analysed through normality tests, homogeneity tests, and Independent Sample t-Test. The results show that the data are normally distributed and homogeneous. The hypothesis test obtained a significance value of 0.000 (< 0.05), indicating a significant difference between the creative thinking abilities of students in the experimental and control classes. Thus, the implementation of the PjBL-based learning module through a Batak Toba traditional building miniature project has proven effective in enhancing the mathematical creative thinking abilities of junior high school students